Use of Case Study Method in Primary School: A Teacher Training Process - KABAPINAR, YÜCEL (My University, 2019)
This study aims to determine how case study method is used in primary school Life_x000D_ Sciences courses in the classroom setting and the change occurred in the quality of_x000D_ in-class use of this method following the case study-based training provided for_x000D_ teachers. This is a qualitative study using the action research design. The study_x000D_ group was composed of 7 second- and third-grade classroom teachers selected from_x000D_ private and state schools under the body of Turkey Ministry of National Education_x000D_ and their 21 students (opinions of 3 students selected from each of 7 classes). The_x000D_ data collection instruments used in the study are the observation form and the semistructured interviews performed with the students. The data obtained were analyzed_x000D_ with the content analysis technique. According to the findings obtained, it was seen_x000D_ that there was a positive change in the quality of how the teachers used the case_x000D_ study method in Life Sciences courses after the case study-based training. It was_x000D_ also concluded that the students liked the courses after the training and thought that_x000D_ they became more active.

Bu araştırmanın amacı ilkokul Hayat Bilgisi derslerinde örnek olay yönteminin sınıf_x000D_ ortamında nasıl kullanıldığını belirlemek ve öğretmenlere verilen örnek olay temelli_x000D_ eğitimin ardından bu yöntemin sınıf içi kullanım niteliğinde ortaya çıkan değişimi_x000D_ tespit etmektir. Araştırma nitel bir çalışma olup, eylem araştırması deseni_x000D_ kullanılmıştır. Araştırmanın çalışma grubunu Milli Eğitim Bakanlığı’na bağlı özel_x000D_ okul ve devlet okullarından seçilen toplam yedi kişiden oluşan 2. ve 3. sınıf öğretmeni_x000D_ ile onların öğrencileri (21 kişi) oluşturmaktadır. Çalışmada kullanılan veri toplama_x000D_ araçları, gözlem formu ve öğrencilerle birebir yapılan yarı yapılandırılmış görüşme_x000D_ formudur. Elde edilen veriler içerik analizi tekniği ile çözümlenmiştir. Elde edilen_x000D_ bulgular doğrultusunda, verilen örnek olay temelli eğitim sonrasında öğretmenlerin_x000D_ örnek olay yöntemini Hayat Bilgisi derslerinde kullanma niteliklerinde olumlu bir_x000D_ değişimin olduğu tespit edilmiştir. Ayrıca öğrencilerin de eğitim sonrasında işlenen_x000D_ dersleri oldukça beğendikleri ve bu şekilde daha aktif olduklarını düşündükleri_x000D_ sonucuna ulaşılmıştır.
İlkokulda Örnek Olay Yönteminin Kullanımı: Bir Öğretmen Eğitimi Süreci